2008
DOI: 10.1007/s10979-007-9113-9
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of opposing expert witnesses for educating jurors about unreliable expert evidence.

Abstract: We tested whether an opposing expert is an effective method of educating jurors about scientific validity by manipulating the methodological quality of defense expert testimony and the type of opposing prosecution expert testimony (none, standard, addresses the other expert's methodology) within the context of a written trial transcript. The presence of opposing expert testimony caused jurors to be skeptical of all expert testimony rather than sensitizing them to flaws in the other expert's testimony. Jurors r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(103 citation statements)
references
References 33 publications
6
95
1
1
Order By: Relevance
“…18,20,25,26,44 A recent analysis found that proceedings featuring opposing medical expert testimony caused jurors to be skeptical of all testimony rather than to select a side they found to be more credible. 30 Medical malpractice litigation and subsequent calls for tort reform have increased appreciably over the past 3 decades, with analyses estimating additional costs to our health care system as high as $10 billion annually from litigations. 1,32,62,63 Given that neurological surgery has the highest proportion of physicians facing a malpractice claim each year (19.1%), a large proportion of these malpractice costs can be attributed to litigation in this field.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…18,20,25,26,44 A recent analysis found that proceedings featuring opposing medical expert testimony caused jurors to be skeptical of all testimony rather than to select a side they found to be more credible. 30 Medical malpractice litigation and subsequent calls for tort reform have increased appreciably over the past 3 decades, with analyses estimating additional costs to our health care system as high as $10 billion annually from litigations. 1,32,62,63 Given that neurological surgery has the highest proportion of physicians facing a malpractice claim each year (19.1%), a large proportion of these malpractice costs can be attributed to litigation in this field.…”
Section: ©Aans 2014mentioning
confidence: 99%
“…Levett and Kovera (2008) found that when mock jurors were presented with opposing expert evidence they became sceptical of all expert evidence. Similarly, Brekke and Borgida (1988) found that when two confl icting expert testimonies were given in simulated rape trials, mock jurors rejected both and relied on their own theories.…”
Section: Theme 9: Rape Misconceptions and Mythsmentioning
confidence: 99%
“…This project demonstrated for the first time that a single expert, testifying without being opposed by an expert retained by the other side, can still be viewed as a hired gun. Previous studies had only examined hired gun experts in the context of two competing experts (Cooper & Neuhaus, 2000;Levett & Kovera, 2008). These research paradigms frequently compared an expert who was highly paid to one who was not, or an expert with impressive credentials to one with less impressive credentials.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this finding occurred with no mention of the expert's pay or frequency of testimony. Levett and Kovera (2008) previously found that the mere presence of an opposing expert caused mock jurors to question the validity of all expert testimony. This skepticism effect was found regardless of the content of the opposing expert's testimony.…”
Section: Hired Gun Effects In Expert Witness Testimonymentioning
confidence: 99%
See 1 more Smart Citation